Trauma, War, and Violence: Public Mental Health in Socio-Cultural Context - Jong, Joop De. (The Springer Series in Social/Clinical Psychology, 2002)
Massive traumatic stress resulting from armed conflict and terrorism is a prime concern of governments, non-government organizations and the United Nations. Yet there is little systematic knowledge of how to address psychological problems of these proportions. These situations are further complicated by the lack of culturally appropriate models for mental health care in many low-income countries. This volume describes a variety of public mental health and psychosocial programs in conflict and post-conflict situations in Africa and Asia. Each chapter details the psychosocial and mental health aspects of specific conflicts and examines them within their sociopolitical and historical contexts. Trauma, War, and Violence: Public Mental Health in Socio-Cultural Context will be of great interest to psychologists, social workers, anthropologists, historians, human rights experts, and psychiatrists working or interested in the field of psychotrauma.